2019
DOI: 10.1145/3329250
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Trust Score on Cooperative Behavior

Abstract: The assessment of trust between users is essential for collaboration. General reputation and ID mechanisms may support users' trust assessment. However, these mechanisms lack sensitivity to pairwise interactions and specific experience such as betrayal over time. Moreover, they place an interpretation burden that does not scale to dynamic, large-scale systems. While several pairwise trust mechanisms have been proposed, no empirical research examines trust score influence on participant behavior. We study the i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Furthermore, we can provide the explanation if we reject or accept a particular network flow, make it easier for engineers to debug the system. By explaining the behavior of the system, we can as well gain the trust of users on the model (Ignat et al , 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we can provide the explanation if we reject or accept a particular network flow, make it easier for engineers to debug the system. By explaining the behavior of the system, we can as well gain the trust of users on the model (Ignat et al , 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The core issue is, machine learning algorithms usually are treated as a black box (Ribeiro et al , 2016), despite many attempts to understand the decisions of these algorithms recently (Roscher et al , 2020). Several studies suggested that lacking understanding in how a system works will lead to the lack of trust from users on the system (Ignat et al , 2019). Furthermore, if we do not understand why does the system make a particular decision, we will be limited in debugging the system, especially when the prediction is wrong.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we will introduce different constraints into the model, for instance the maximum loss one can resist while using a model. Another approach is to integrate simulated behavior of users in non-cooperative or cooperative markets [5,16].…”
Section: Discussionmentioning
confidence: 99%
“…The MATG, first published by Collins 1 in his master’s thesis, is a game of strategic interaction combining features of two commonly used games, the multi-arm bandit game ( Robbins, 1952 ) and the trust game ( Berg et al, 1995 ). The trust game was first used by Berg et al (1995) to examine behavior in one-shot interactions and later used by other researchers to study behavior in repeated interactions ( Dubois et al, 2012 ), group interactions ( Ignat et al, 2019 – control condition), and over various periods of time ( Strachan et al, 2020 ). The multi-arm bandit game ( Robbins, 1952 ) has been used in various psychological studies to explore exploration-exploitation behavior in both animals and humans (e.g., Cohen et al, 2007 ).…”
Section: Empirical Study Methodsmentioning
confidence: 99%